Controls on the stratal architecture of lacustrine delta successions in low‐accommodation conditions. Issue 5 (26th January 2021) - Olariu, Cornel; Zhou, Chuanmin; Steel, Ronald; Zhang, Zhijie; Yuan, Xuanjun; Zhang, Jinyu; Chen, Si; Cheng, Dawei; Kim, Wonsuck
Abstract: Lake‐delta deposits in low‐accommodation conditions are only a few metres thick and in some cases non‐existent. Fluvial channels occur in many cases directly on top of fine‐grained lacustrine deposits with delta deposits apparently missing. The geomorphology and stratigraphy of modern deltas in Lake Eyre, Australia, and Lake Chad in Africa indicate that delta shorelines can develop in lakes, but in many cases build out into low‐accommodation settings due to highly dynamic lake‐water levels. This work suggests that low‐accommodation is critical in the development of lacustrine delta deposits and that high (frequency and magnitude) rates of lake‐level change result in 'telescoping' deltas, the deposits of which are thin but extensive. The telescopic deltas have conformable beds, but with abrupt vertical facies changes; this apparent stratigraphic contradiction is the result of long horizontal distance translation of the depositional system. Details of two lacustrine units, in Uinta Basin in the USA and Junggar Basin in China, both of which show characteristics of telescoping, are used to develop a process based stratigraphic model for the deposits of such lake deltas. Lacustrine facies comprise cross‐stratified, ripple cross‐laminated, structureless or graded and sharp‐based sandstone beds, mudstone (structureless, laminated, rippled, rich in organic content), carbonate mudstone, ooid packstone and stromatolites. Three facies associations are critical for lake delta stratigraphy: channelized distributary deposits that occur in the delta topset; lake plain deposits that represent the fluvial overbank deposits and the subaerially exposed (at low lake level) lake deposits; and fine‐grained, lacustrine deposits. A key corollary of the proposed low‐gradient, telescoping lacustrine delta model is that broad and shallow channels dominate the system, but that decimetre to metre thick, gently dipping delta‐front beds form subtle deposits along the margins of the lakes. These delta depocentres migrate basinward and landward at high rates (tens of kilometres each year), building thin (metres) but laterally extensive (tens of kilometres) sandstone units through multiple transgression–regression cycles.